INTERNATIONAL CAPITAL FLOWS INTO AND ACROSS UKRAINE - Savelyev, Yevhen (Journal of European Economy, 2005)
The paper reviews on theoretical basis international capital flow movements. It proposes few new trends that exist in the capital markets, the way changes are taking place in Ukrainian financial market and its further integration in the world market. The paper proposes few ways in which, a financial offshore center can be created in Ukraine. It also discusses the advantages of having a financial offshore center in Ukraine at both political and economic levels.